INNOVATIVE TEACHING STRATEGIES FOR ENHANCING THE USE OF DESIGNATED ENGLISH PHRASES - Nephawe, Farisani Thomas; Miftah, M. Zaini (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
The present study investigated innovative teaching strategies to strengthen the use of designated English phrases at a rural-based university. The study adopted a quantitative research approach with quasi-experimentation for the pre-test and post-test results to identify innovative strategies for enhancing the use of these phrases. A descriptive research design was used to describe the status of these strategies accurately. Thirty (30) students registered in English Module 2561in the First Semester of the 2023 academic year were randomly sampled to participate in the study. Data were collected using a questionnaire, which provides flexibility and accuracy for selecting answers from the given multiple-choice questions. The Statistics Package for Social Sciences (SPSS) version 29.0 was employed to analyse the findings due to its new enhancements to manage large and complex data sets. The pilot study revealed that students were incompetent in using designated English phrases. However, students performed remarkably after utilising blended learning and Jigsaw strategies. The study implies that the identified strategies are indispensable to enhancing the use of designated English phrases. Further research should be conducted studies on the indispensability of the identified strategies. The study recommends frequently using the identified strategies to enhance the use of designated English phrases.